Ex Vivo treatment of coronary artery endothelial cells with serum post-exercise training offers limited protection against in vitro exposure to FEC-T chemotherapy - Mclaughlin, Marie; Hesketh, Katie L.; Horgan, Sarah L.; Florida-James, Geraint; Cocks, Matthew; Strauss, Juliette A.; Ross, Mark (Frontiers in Physiology, 2023)
Background: Chemotherapy treatment for breast cancer associates with well-documented cardiovascular detriments. Exercise has shown promise as a potentially protective intervention against cardiac toxicity. However, there is a paucity of evidence for the benefits of exercise on the vasculature. Objectives: This study aimed to determine the effects of chemotherapy on the vascular endothelium; and if there are protective effects of serological alterations elicited by an exercise training intervention. Methods and Results: 15 women participated in a 12-week home-based exercise intervention consisting of three high-intensity interval sessions per week. Human coronary artery endothelial cells (HCAEC) were exposed to physiological concentrations of 5-fluorouracil, epirubicin, cyclophosphamide (FEC) and docetaxel to determine a dose-response. Twenty-four hours prior to FEC and docetaxel exposure, HCAECs were preconditioned with serum collected pre- and post-training. Annexin V binding and cleaved caspase-3 were assessed using flow cytometry and wound repair by scratch assays. Chemotherapy exposure increased HCAEC Annexin V binding, cleaved caspase-3 expression in a dose-dependent manner; and inhibited wound repair. Compared to pre-training serum, conditioning HCAECs with post-training serum, reduced Annexin V binding (42% vs. 30%, p = 0.01) when exposed to FEC. For docetaxel, there were no within-group differences for Annexin V binding or cleaved caspase-3 expression. There was a protective effect of post-training serum on wound repair for 5-flurouracil (p = 0.03) only. Conclusions: FEC-T chemotherapy drugs cause significant damage and dysfunction of endothelial cells. Preconditioning with serum collected after an exercise training intervention, elicited some protection against the usual toxicity of FEC-T, when compared to control serum.